Efektivitas Terapi Adjuvan Citicoline terhadap Perbaikan Kognitif Pasien Cedera Kepala - Ramadhan, Syafira Elfa; Putri, Nikmatul Hikmah; Sulistio, Bayu; Sari, Fery Luvita (Cermin Dunia Kedokteran, 2024)
Background: Head injuries can reduce brain function with high morbidity. Several studies showed that citicoline may improve mild, moderate, and severe head injuries. Objective: To review the effectiveness of citicoline for cognitive improvement in head injury patients. Methods: Systematic search of 2 databases, ScienceDirect and Pubmed. Selected articles were then critically reviewed and analyzed. Results: Studies by Levin (1991) and Calatayud, et al, (1991) in Secades, et al. (2021); and Shokouhi, et al, (2014) showed that citicoline may improve cognitive function in adults and elderly with mild, moderate, and severe head injuries (p <0.05). Conclusion: Citicoline is effective in improving cognitive function in head injury patients.